Innovation in Santa Catarina’s industries: exploring the relationship between contingency factors and management control systems - Ana Caroline Romão da Silva; Alcindo Cipriano Argolo Mendes; Carlos Eduardo Facin Lavarda (Contabilidad y Negocios: Revista del Departamento Académico de Ciencias Administrativas)
This study aims to analyze the manner in which contingency factors have an influence in the application of management control systems based on Simons’ Levers of Control model (1995) and, consequently, its impact on innovation in Santa Catarina’s industries. To such aim, a descriptive and quantitative research was carried out with 79 industries from different sectors from Santa Catarina; descriptive statistics and structural equation models were employed for data analysis. Findings revealed that the interactive use of SGC prevails when aiming at fostering product and process innovation, while the diagnostic use did not show a significant influence. In addition, it was evidenced that no relationship existed between the environmental uncertainty and the interactive use or SGC diagnosis. Finally, findings reveal that organizational practices, such as SGC use and innovation, are implemented by the analyzed companies, not considering external factors like the market, politics and customers.